Molecular Docking of Key Compounds from Acacia Honey and Nigella sativa Oil and Experimental Validation for Colitis Treatment in Albino Mice - Mehwish Bibi; Irfan Baboo; Hamid Majeed; Santosh Kumar; Maximilian Lackner (Biology)
Colitis, an inflammatory condition of the colon that encompasses ulcerative colitis (UC) and Crohn’s disease, presents significant challenges due to the limitations and side effects of current treatments. This study investigates the potential of natural products, specifically AH and NSO, as organic therapeutic agents for colitis. Molecular docking studies were conducted to identify the binding affinities and interaction mechanisms between the bioactive compounds in AH and NSO and proteins implicated in colitis, such as those involved in inflammation and oxidative stress pathways. An in vivo experiment was performed using an albino mouse model of colitis, with clinical symptoms, histopathological assessments, and biochemical analyses conducted to evaluate the therapeutic effects of the compounds both individually and in combination. Results from the molecular docking studies revealed promising binding interactions between fructose and Prostaglandin G/H synthase 2 (Ptgs2) and between fructose and cellular tumor antigen p53, with docking energy measured at −6.0 kcal/mol and −5.1 kcal/mol, respectively. Meanwhile, the presence of glucose molecule glucokinase chain A (−6.3 kcal/mol) and chain B (−5.8 kcal/mol) indicated potential efficacy in modulating inflammatory pathways. Experimental data demonstrated that treatment with AH and NSO significantly reduced inflammation, improved gut health, and ameliorated colitis symptoms. Histopathological evaluations confirmed reduced mucosal damage and immune cell infiltration, while biochemical analyses showed normalization of inflammatory markers and oxidative stress levels. This study provides compelling evidence for the potential of AH and NSO as natural, complementary treatments for colitis, suggesting their future role in integrative therapeutic strategies. However, further research into long-term safety, optimal dosing, and mechanisms of action is warranted to translate these findings into clinical applications.